Goosebumps: How I Got My Shrunken Head - Stine, R L (Scholastic Ltd, 1996)
Mark's Aunt Benna presents him with a gift of a shrunken head from the jungle island of Baladora, which gives Mark a strange, dangerous power.
Keywords: Horror & Ghost Stories; Juvenile Fiction